2006
DOI: 10.2527/2006.843608x
|View full text |Cite
|
Sign up to set email alerts
|

Performance, diarrhea incidence, and occurrence of Escherichia coli virulence genes during long-term administration of a probiotic Enterococcus faecium strain to sows and piglets1

Abstract: As part of an interdisciplinary research project, the performance response of sows and their litters to the probiotic strain Enterococcus faecium NCIMB 10415, as well as some health characteristics of the piglets, were studied. Gestating sows (n = 26) were randomly allotted into 2 groups. The probiotic was administered by dietary supplementation to 1 group of sows and their respective litters (probiotic group), whereas the second group (control group) received no probiotic supplementation. The duration of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
3
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 24 publications
(35 reference statements)
5
97
3
10
Order By: Relevance
“…Herranz et al (2001) observed among LAB including some E. faecium strains as nonpathogenic with an ability to produce lactic acid and bacteriocin. In animal management, E. faecium have received more attention as probiotic preparations, such as, in pigs (Macha et al 2004;Scharek et al 2005;Taras et al 2006) and poultry due to having immune system stimulating properties in host and protect animals from gastrointestinal diseases (Taras et al 2006;Vahjen et al 2002). Since E. faecium Pb12 strains survived in the fish intestine without exhibiting the pathogenicity, further experiments were carried out using only this LAB strain among five.…”
Section: Viability Of Bacteria Within Fish Intestinal Milieumentioning
confidence: 99%
“…Herranz et al (2001) observed among LAB including some E. faecium strains as nonpathogenic with an ability to produce lactic acid and bacteriocin. In animal management, E. faecium have received more attention as probiotic preparations, such as, in pigs (Macha et al 2004;Scharek et al 2005;Taras et al 2006) and poultry due to having immune system stimulating properties in host and protect animals from gastrointestinal diseases (Taras et al 2006;Vahjen et al 2002). Since E. faecium Pb12 strains survived in the fish intestine without exhibiting the pathogenicity, further experiments were carried out using only this LAB strain among five.…”
Section: Viability Of Bacteria Within Fish Intestinal Milieumentioning
confidence: 99%
“…Similar results were obtained by Estienne et al (2005), when the authors observed weight gain and satiety for weaning pigs after receiving probiotics and housed in a mixture of litters. However, Taras et al (2006) found no effect of the probiotic on the performance of the animals after weaning. According to these studies, the variation in results obtained from the literature may be related to genetics, the strain used as probiotic and especially to environmental conditions.…”
Section: Resultsmentioning
confidence: 81%
“…According to Taras et al (2006), while studies with pigs and poultry have shown that probiotics have a positive effect on the feces, many of them show only a slight improvement in weight gain and feed conversion. According to these authors, the challenge may not be high enough to show the benefit of the use of probiotics on this factor.…”
Section: Resultsmentioning
confidence: 99%
“…Among others, the use of probiotics such as lactobacilli and bifidobacteria has been proposed as the most promising approach for maintaining or improving animal health (Stein and Kil, 2006;Lalles et al, 2007). It has been reported that feeding certain probiotic strains to pigs could improve growth performance, prevent the growth of pathogenic bacteria and reduce the incidence of diarrhea (Shu et al, 2001;Gardiner et al, 2004;Taras et al, 2006;Casey et al, 2007). At the same time, feeding an FLD prepared with the use of bacteria, such as lactic acid bacteria, has also been shown to improve pig performance and to reduce the number of enteric pathogens (Canibe and Jensen, 2003;Stein and Kil, 2006).…”
Section: Introductionmentioning
confidence: 99%